Clinical experience with an epoxy resin adhesive for direct bonding of orthodontic attachments* - Dijkman, J. F. P.; Retief, D. H. (My University, 1972)
An epoxy resin formulation developed in the Dental Research Unit has been subjected to further clinical trials. Six patients, were used in the study. They were divided into two age groups and all the teeth, including the first molars, bonded. Rubber dam was used to keep the crowns dry during the setting period of the resin. In the younger group the mean failure rates were 27 per cent for anterior teeth and 70 per cent for the first molars. In the older group these rates were 11 per cent for incisors, 11 per cent for canines, 20 per cent for premolars and 20 per cent for first molars. While no figures are available in the literature relating to direct bonding to first molars, the results obtained in this study for the other teeth compare favourably with data previously published by other authors after trials using other types of cement.
KIM
Keywords: Dental Bonding; Epoxy Resins; Orthodontic Appliances